Message Oriented Middleware For Library’s Metadata Exchange - Ni Wayan Wisswani; I Wayan Kandi Wijaya (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Library is one of the important tools in the development of science to store various intellectual properties. Currently most libraries are managed by standalone systems and are not equipped with data exchange facilities with other libraries for sharing information. Sharing of information between libraries can be done with integration metadata owned library. In this research, the integration architecture of metadata exchange is done with Message Oriented Middleware (MOM) technology. This MOM redeems the collection metadata that matches the standard Dublin Core format. In this research, database structure, MOM structure and set of rules to perform data sharing process. With the proposed MOM architectural design is expected to search process information between libraries will become easier and cheaper.